KNOWLEDGE SHARING IMPACT ON TEAM PERFORMANCE: UNPACKING THE ROLE OF ABSORPTIVE CAPACITY IN IT BASED INDUSTRY IN PAKISTAN - Ali Raza; Bilal Idrees; Ali Hassan; Arslan Arshad; Soban Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
Purpose: The current study used to investigate how Coworker knowledge sharing affects team performance through the mechanism of Absorptive capacity, Coworker knowledge sharing makes it easier to share information, skills, and expertise—all of which are essential for improving team performance. This study investigates how this link is mediated by a team’s absorptive capacity, which is characterized as its potential to value new information, digest it, and use it for commercial purposes. Design/ methodology/approach: The convenient sampling method was used to gather data. 183 mid-level workers in Pakistan’s IT sector provided data for the study using standardized questionnaires. With SPSS, correlation and regression analysis were used to analyze the data. Findings: According to our research, there is a considerable correlation between high absorptive capacity and the beneficial benefits of coworker knowledge sharing on team performance. Strong absorptive capacities enable teams to take full use of the knowledge that is shared among them, which improves creativity, problem-solving, and general productivity. In order to maximize team performance, this research emphasizes how crucial it is to create an environment that encourages information exchange as well as the growth of absorptive ability. Originality/value: Both theoretical and practical ramifications follow from them. Future research objectives and managerial implications are offered to assist organizational leaders in fostering creativity in the face of complexity and diversity.